Challenges of adopting entrepreneurship education as a strategic approach to unemployed-youth in South Africa - Ngcobo, Sanele; Khumalo, Njabulo (Technium Social Sciences Journal, 2022)
Due to the level of unemployment rate in South African among the young, the paper seeks to assess the adoption of entrepreneurship education as a strategic approach to curb youth unemployment within a District Municipality public high schools in KwaZulu-Natal South Afrrica. The target population was 489 principals from high schools within the within the District Municipality. A mixed methods approach was used and a questionnaire was constructed and administered to participants via online platform. Also, an online one on one interviews were conducted with principals. All data was analysed using SPSS version 25 that generate data into table and bar graphs. The paper revealed that they are many challenges with the adoption of entrepreneurship and these challenges include financial challenge, lack of entrepreneurship education in public schools and lack of support. Small Enterprise Finance Agency (SEFA), National Youth Development Agency (NYDA), Department of Trade and Industry (DTI), Small Enterprise Development Agency (SEDA) and National Empowerment Fund (NEF) should run more awareness campaigns on media platforms used by students and the youth to promote entrepreneurship.